Cultivating School Counseling Leaders Through District Leadership Cohorts. Issue 1 (2017) - Kneale, Marcy G. Miller; Young, Anita A.; Dollarhide, Colette T.
Demonstrating effective leadership skills is a necessity for school counselors seeking to achieve a systemic vision that influences change. The challenge becomes the delivery of training methods that allow school counselors and school counseling supervisors to develop leadership skills, gain confidence, and maximize their potential. This article presents district cohort training approaches that can enhance the leadership capacity of pre-K–12 school counselors and school counseling supervisors.